Main factors controlling hydrocarbon accumulation in the Northwestern Sichuan Basin - Xiao, Hang; Xu, Fanghao; Fu, Xiaodong; Li, Wenzheng; Chen, Cong; Zhang, Jianyong; Wang, Yajie; Zhou, Kuan (Frontiers in Earth Science, 2022)
The Basin-mountain transition regions of the foreland basins are the hot spots for hydrocarbon exploration worldwide, while the complex geological features and hydrocarbon accumulation rules make hydrocarbon exploration there a very difficult job. The Northwestern Sichuan Basin is a typical case, where the unclear distribution rules restrict the further exploration of natural gas. In this study, geochemistry and seismic profile data were comprehensively used to reveal the main factors controlling hydrocarbon accumulation in the Northwestern Sichuan Basin. The Lower Cambrian and the Upper Permian source rocks have different carbon isotope composition, indicating they have different kerogen type, humic kerogen for the Lower Cambrian source rocks and humic and mixed kerogen for the Upper Permian source rocks. The Northwestern Sichuan Basin can be divided into the unfaulted belt, the thrust front belt and the thrust nappe belt. The thrust nappe belt develops many large thrust faults, and the natural gas there mainly originates from the Lower Cambrian source rocks. However, due to different denudation of regional caprocks, hydrocarbons in the area adjacent to the Longmenshan fold-and-thrust system were destroyed while in the area adjacent to the thrust front belt had a good preservation condition. The thrust front belt and the unfaulted belt develop a few or few thrust faults, and the natural gas there mainly originates from the Upper Permian source rocks and have a good preservation condition due to no denudation of regional caprocks. The distribution of thrust faults controls the natural gas origins in different areas and the preservation condition determines whether the gas reservoirs can survive to the present or not. These conclusions can provide the guidance for natural gas exploration in the Northwestern Sichuan Basin and also other basin-mountain transition regions in the foreland basins over the world.